Anesthetic Management of Total Aortic Arch Replacement in a Myasthenia Gravis Patient under Deep Hypothermic Circulatory Arrest - Mamiko Kondo; Yusuke Yoshikawa; Hirofumi Terada; Michiaki Yamakage (Case Reports in Anesthesiology)
The anesthetic management of myasthenia gravis patients undergoing cardiac or aortic surgery under cardiopulmonary bypass, especially with deep hypothermic circulatory arrest, is challenging. We describe a case of successful anesthetic management of a myasthenia gravis patient undergoing total arch replacement with deep hypothermic circulatory arrest under neuromuscular monitoring and complete reversal of the action of neuromuscular blocking drugs by sugammadex. The present case suggests that patients with well-controlled myasthenia gravis might be safely managed in cardiac or aortic surgery under cardiopulmonary bypass with deep hypothermic circulatory arrest.